Cloning, expression and characterization of glycerol dehydrogenase involved in 2, 3-butanediol formation in Serratia marcescens H30. (1st September 2014) - Zhang, Liaoyuan; Xu, Quanming; Peng, Xiaoqian; Xu, Boheng; Wu, Yuehao; Yang, Yulong; Sun, Shujing; Hu, Kaihui; Shen, Yaling
Abstract: The meso -2, 3-butanediol dehydrogenase ( meso -BDH) from S. marcescens H30 is responsible for converting acetoin into 2, 3-butanediol during sugar fermentation. Inactivation of the meso -BDH encoded by bud C gene does not completely abolish 2, 3-butanediol production, which suggests that another similar enzyme involved in 2, 3-butanediol formation exists in S. marcescens H30. In the present study, a glycerol dehydrogenase (GDH) encoded by gld A gene from S. marcescens H30 was expressed in Escherichia coli BL21(DE3), purified and characterized for its properties. In vitro conversion indicated that the purified GDH could catalyze the interconversion of (3 S )-acetoin/ meso -2, 3-butanediol and (3 R )-acetoin/(2 R, 3 R )-2, 3-butanediol. (2 S, 3 S )-2, 3-Butanediol was not a substrate for the GDH at all. Kinetic parameters of the GDH enzyme showed lower K m value and higher catalytic efficiency for (3 S /3 R )-acetoin in comparison to those for (2 R, 3 R )-2, 3-butanediol and meso -2, 3-butanediol, implying its physiological role in favor of 2, 3-butanediol formation. Maximum activity for reduction of (3 S /3 R )-acetoin and oxidations of meso -2, 3-butanediol and glycerol was observed at pH 8.0, while it was pH 7.0 for diacetyl reduction. The enzyme exhibited relative high thermotolerance with optimum temperature of 60 °C in the oxidation–reduction reactions. Over 60 % of maximum activity was retained at 70 °C. Additionally, the GDH activity was significantly enhanced for meso -2, 3-BD oxidation in the presence of Fe 2+ and for (3 S /3 R )-acetoin reduction in the presence of Mn 2+, while several cations inhibited its activity, particularly Fe 2+ and Fe 3+ for (3 S /3 R )-acetoin reduction. The properties provided potential application for single configuration production of acetoin and 2, 3-butanediol .